Pengembangan Sumber Daya Aparatur Dalam Rangka Meningkatkan Kinerja - Sulistiono, Slamet (Jurnal Administrasi Publik, 2013)
Abstract: Human resource is a valuable asset in both organization and institution. Therefore, human factor as the most important element that must be well-managed through planning, organizing, directing, and monitoring, and also evaluating in order to improve service, quality, expertise, ability, and skill in carry out the duty efficiently and efficiently in order to achieve the organization’s goal. This research aims to understand the efforts which conducted by BKD Malang in personnel resources development as well as to understand the enabling and inhibiting factors in the implementation of personnel resources development. The efforts of personnel resources development in order to improve the performance of employee in BKD Malang has done through education and training as well as promotion and transfer processes. In the conduct of education and training was done by sending the employee through selection process to participate in education and training, and also sending the employee to attend the formal education. In the implementation of personnel resources development which done by BKD Malang is inseparable from enabling and inhibiting factors. The enabling factors of personnel resources development are all requirements and needs also the processes and activities in accordance with the prescribed running. While the first inhibiting factor is age factor, the absence of a clear result of the assignment of an employee to attempt the formal training in educational institutions Keywords : development, human research, performance. Abstrak: Sumber Daya Manusia (SDM) mrupakan Suatu asset yang berharga dalam Suatu Organisasi maupun instansi. Oleh sebab itu maka faktor manusia sebagai unsur yang paling penting yang harus dikelola dengan baik melalui perencanaan, pengorganisasian, pengarahan, dan pengawasan serta evaluasi sehingga dapat meningkatkan pengabdian, mutu, keahlian, kemampuan, dan keterampilan dalam melaksanakan tugas secara berdaya guna dan berhasil guna dalam pencapaian tujuan organisasi. Penelitian ini bertujuan untuk mengetahui bagaimana upaya yang dilakukan oleh BKD Kota Malang dalam pengembangan sumber daya aparatur serta untuk mengetahui faktor pendukung dan penghambat dalam pelaksanaan pengembangan sumber daya aparatur. Upaya pengembangan sumber daya aparatur dalan rangka meningkatkan kinerja pegawai di BKD Kota Malang dilakukan melalui pendidikan dan pelatihan (diklat) serta proses promosi dan mutasi. Dalam melakukan pendidikan dan pelatihan dilakukan dengan mengirim pegawai melalui proses seleksi untuk mengikuti pendidikan dan latihan serta dilakukan dengan mengirim pegawai untuk mengikuti pendidikan formal. Dalam pelaksanaan pengembangan sumber daya aparatur yang dilakukan oleh BKD Kota Malang tidak terlepas dari faktor pendukung dan penghambat. Faktor pendukung proses pengembangan sumber daya aparatur adalah segala persyaratan dan kebutuhan serta proses kegiatan terpenuhi dan berjalan sesuai dengan yang ditentukan. Sedangkan faktor penghambatnya yang pertama ialah faktor usia, tidak adanya hasil yang jelas dari upaya penugasan pegawai untuk mengikuti pendidikan formal di instansi pendidikan. Kata Kunci: Pengembangan, Sumber Daya Manusia, Kinerja